24.8k views
5 votes
3x^2+12x+12 solve or factor the equation

User Brittanie
by
4.8k points

2 Answers

2 votes

Answer:

3(x+2) (x+2)

Explanation:

Given 3x²+12x+12

We expand the equation

That is,

3x²+6x+6x+12

We add parentheses to factor out

(3x²+6x)+(6x+12)

3x(x+2)+6(x+2) > Taking out the

common factors.

(3x+6) (x+2)

= 3(x+2) (x+2)

User Jared Beach
by
5.7k points
6 votes

Answer:

x = -2 (multiplicity 2).

Explanation:

3x^2+12x+12 = 0

3(x^2 + 4x + 4) = 0

3(x + 2)(x + 2) = 0

x = -2 (multiplicity 2).

2 roots - both equal.

User Swagath
by
5.6k points